Quantum mechanics for nuclear structure. - Heyde, Kris L. G., 1942-; Wood, J. L. (John L.), 1941- (IOP ebooks. 2020 collection., 2020)
The first volume of Quantum Mechanics for Nuclear Structure introduced the reader to the basic elements that underpin the one-body formulation of quantum mechanics. Volume two follows on from its predecessor by examining topics essential for understanding the many-body formulation. The algebraic structure of quantum theory is emphasised throughout as an essential aspect of the mathematical formulation of many-body quantum systems. Part of IOP Series in Nuclear Spectroscopy and Nuclear Structure.